Erythrocyte arginase activities in inactive lepromatous leprosy patients - Ozan, S. Temizer; Erisir, M.; Yilmaz, S.; Ozan, G.; Seyran, A. (Blackwell Publishing, 2006)
[Abstract Not Available]
31st Congress of the Federation-of-European-Biochemical-Societies (FEBS) -- JUN 24-29, 2006 -- Istanbul, TURKEY